Time-depth recorders attached to chick-rearing murres in 2009 - Elliott, Kyle H.; Hare, James F.; Le Vaillant, Maryline; Gaston, Anthony J.; Ropert-Coudert, Yan; Anderson, W. Gary (Dryad Digital Repository, 2014)
Output from various Lotek time-depth recorders. Refer to the same folders from each year for chick-rearing birds for information on the format of each file type. In 2004, some birds had handicaps attached and 2004 data were therefore excluded from analyses. In 2008, because of an error in the programming of the tag, the actual pressure reading is 1/4 the reported reading and therefore the conditional log filled rapidly.